Os temperamentos hipocráticos e a suscetibilidade do adoecer das mulheres na pós-menopausa - Pirolo, Eliana [UNIFESP] (2016)
During menopausal transition and in the post-menopause, apart from symptons of hypoestrogenism, chronic diseases frequently arise, such as diabetes mellitus, systemic arterial hypertension and osteoporosis. Besides knowing that each living being reacts differently to effects that are related to the same cause, and that susceptibility is the individual tendency of suffering dynamic influences and of developing symptoms or diseases, homeopathy, taught us that we have genetically inherited our complexion and temperament and along with them our probable way of falling ill. Homeopathy utilizes the study of complexions and temperaments as a diagnostic resource in the semiology of the assessment of a patient's susceptibility to specific diseases, helping to elect an appropriate medicine. A transversal study was carried out on 200 women aged between 50 and 65 (post-menopause period), assisted at the Menopausal Transition and Post-Menopause Ambulatory managed by the Endocrinology Ginecology Discipline at Universidade Federal de São Paulo - Escola Paulista de Medicina [Federal University of Sao Paulo - Medicine School], previously classified according to the evaluation criteria of temperaments proposed by Hippocrates, divided intolymphatic, sanguine, biliary and atrabiliary. Women with lymphatic temperament presented a higher level of hydric retention and hypothyroidism and less often vasomotor symptons; weight gain and obesity were similar to sanguine temperament women and these in turn showed vasomotor symptons similar to patients with biliary and atrabiliary temperaments as well as lower prevalence of anger, melancholy and sadness. The frequency of heart disease was higher in the biliary group and also had the lowest number of cases of osteoporosis. Women with atrabiliary temperament presented a higher level of insomnia, hyperthyroidism, osteoporosis, fibromyalgia, periodontitis, irritability and nervousness. The cases of depression were similar to the biliary ones. From the psychic point of view, the sanguine subjects were happy and optimistic, whereas lymphatic women were sad and melancholic. Atrabiliary women presented higher irritability and mood swings, while the biliary temperament ones appeared authoritarian, impatient and ambitious. It has been possible to assess the process of developing diseases which occurs in post-menopause women in light of their temperaments, considering both psychological and physical symptoms as well as the endocrinologic profile of the patients.